Digital Inclusion and Accessibility E-Government in the Padang City - Cancer Rusnita, Widya; Koeswara, Hendri; Ekha Putera, Roni; Kusdarini, Kusdarini; Aldelano Azre, Ilham; Kusumi Rahayu, Wewen (Iapa Proceedings Conference, 2024)
The implementation of e-government in Indonesia continues to evolve alongside the transformation of public services into digital formats. This article aims to analyze the level of inclusiveness and accessibility of e-government services in the Padang City using the Technology Acceptance Model (TAM) approach. This research focuses on how the perceived usefulness and perceived ease of use of digital services affect public acceptance of this technology. The research method employed is qualitative descriptive, with data collected through interviews, observations, and document analysis. The findings indicate that although digital services in Padang offer numerous benefits, significant challenges remain in ensuring accessibility for vulnerable groups, including persons with disabilities. This article recommends enhancing accessibility features in e-government applications and implementing policies that support digital inclusiveness across all sectors of society.